2007
DOI: 10.1209/0295-5075/77/36004
|View full text |Cite
|
Sign up to set email alerts
|

Modulated Hexatic-B* with giant electroclinic effect rather than anticlinic Hexatic-I A * —A novel mechanism for stabilizing antiferroelectricity below Smectic-C A *

Abstract: The antiferroelectric hexatic phase observed below antiferroelectric SmC * A has so far been considered to have the same anticlinic structure as in SmC *A . The orientational order parameter determined by infrared spectroscopy distinctively disproves the previous view and concludes that molecular long axes are not tilted from the SmA layer normal. The phase can be identified as non-tilted modulated HxB * and the electric-field-induced phase transition from this phase to tilted ferroelectric HxI * can be consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“…We have selected the average < | cos γ| > as a simple surrogate of the layer spacing [21], i.e., we assume that the spacing can be approximated by the average projection of the molecules onto the layer normal. This assumption is supported by recent experimental data [22] which indicate that for several different compounds there exists a good correlation between the temperature vari- ation of the smectic period d and the order parameter S k . At the same time, < | cos γ| >≈ 1 − 0.5 < sin 2 γ > and S k = 1 − 1.5 < sin 2 γ >, which yields < | cos γ| >≈ (2 + S k )/3.…”
supporting
confidence: 71%
“…We have selected the average < | cos γ| > as a simple surrogate of the layer spacing [21], i.e., we assume that the spacing can be approximated by the average projection of the molecules onto the layer normal. This assumption is supported by recent experimental data [22] which indicate that for several different compounds there exists a good correlation between the temperature vari- ation of the smectic period d and the order parameter S k . At the same time, < | cos γ| >≈ 1 − 0.5 < sin 2 γ > and S k = 1 − 1.5 < sin 2 γ >, which yields < | cos γ| >≈ (2 + S k )/3.…”
supporting
confidence: 71%
“…Antiferroelectric hexatic phase does not always emerge below antiferroelectric SmC Ã A , but ferroelectric hexatic phase appears instead of antiferroelectric hexatic phase at around 50% MHOBMB. The phases they identified as HxI Ã A and HxI Ã must be antiferroelectric and ferroelectric modulated HxB's, respectively, for the smectic layer spacing changes with temperature as pointed out by Korlacki et al [18]. When both modulated HxB's emerge below SmC Ã A at about 63% MHOBMB, the antiferroelectric one always appears above the ferroelectric one; this is understandable as the formation of the closed contour loops needs an increase in entropy, although the emerging order is just opposite to the case of SmC Ã and SmC Ã A .…”
Section: Liquid Crystals 871mentioning
confidence: 85%
“…and then proceed to the unexpected conclusion made by Korlacki et al [18]: The 'antiferroelectric' phase that had been so far identified as 'anticlinic HxI Ã A ' is 'modulated HxB' and the electric-field-induced phase transition from this phase to tilted HxI Ã is the giant electroclinic effect due to the opening of closed modulation loops.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations